Effectiveness of Sanitization Assessment by ATP Bioluminescence Detection System as a Complementary Method in Vivarium: A five-year status report (Journal of Laboratory Animal Science, 2024)
Sanitization is an important activity performed in the laboratory animal facilities and periodical  assessment of sanitization provides confidence in surface cleanliness as well as health status of  animals in the vivarium. The primary objective was to evaluate routine disinfection and/or sanitization  practices upon verifying the adenosine triphosphate (ATP) bioluminescence method, which further  expressed as relative light units (RLU), a relatively easy and rapid method to interpret results within a  minute after the swab sampling performed on any surface. A five-year data compilation showed that  RLU values were within the in-house acceptable limits of animal rooms sampled from racks, isolators,  doors, trolleys, cage changing stations, tables, walls and cage accessories. However, some of the  materials such as racks and trolleys of high-traffic areas showed a significant increase in RLU values  due to organic matters that might be present on the equipment surfaces but recorded values were well  within the limits set by the facility. Additionally, contact plates were also used as confirmatory method  to evaluate microbial monitoring in animal rooms including cage accessories and further historical  values of RLU provided confidence to increase monthly contact plate sampling interval to a quarterly  basis and followed as per the schedule. Moreover, representative samples from incoming animals were  screened by microbial monitoring at regular intervals during the quarantine period and active sentinel  samples also screened for serology or PCR as part of comprehensive health monitoring program. In  conclusion, ATP method can be used to assess the real-time effectiveness of sanitization practices in  vivarium as it provides immediate feedback to animal care personnel that enables corrective actions;  hence the ATP bioluminescence is continued as one of the complementary methods at our laboratory  animal facility.
Keywords: Adenosine triphosphate (ATP); Bioluminescence; Luminometer; Rapid microbiology; Relative Light Units (RLU); Vivarium Sanitization